1982
DOI: 10.1142/s0192415x82000178
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Therapy for the Treatment of Tobacco Smoking Addiction

Abstract: Acupuncture has been reported as an effective treatment for some addictions. The purpose of this study was to evaluate acupuncture treatment effect on the cigarette smoking habit with a motivated population in a controlled clinical setting. From a volunteer research population, sixteen matched pairs were assembled according to age, sex, and severity of smoking habit. Research subjects were randomly assigned to real or sham acupuncture treatment groups. Self-reported cigarette logs were measured pre-treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Research in this area has been conducted over a long period. Four studies were published in the 1970s (Gilbey 1977;Lacroix 1977;Parker 1977a;Vibes 1977), ten in the 1980s (Circo 1985;Clavel 1985;Cottraux 1983;Gillams 1984;Labadie 1983;Lagrue 1980;Lamontagne 1980;Martin 1981a;Steiner 1982;Vandevenne 1985), eight in the 1990s (Clavel 1992;Georgiou 1999;He 1997;Leung 1991;Pickworth 1997;Tian 1996;Waite 1998;White 1998), and the remainder since 2000.…”
Section: Figure 1 Flow Diagram For Update 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…Research in this area has been conducted over a long period. Four studies were published in the 1970s (Gilbey 1977;Lacroix 1977;Parker 1977a;Vibes 1977), ten in the 1980s (Circo 1985;Clavel 1985;Cottraux 1983;Gillams 1984;Labadie 1983;Lagrue 1980;Lamontagne 1980;Martin 1981a;Steiner 1982;Vandevenne 1985), eight in the 1990s (Clavel 1992;Georgiou 1999;He 1997;Leung 1991;Pickworth 1997;Tian 1996;Waite 1998;White 1998), and the remainder since 2000.…”
Section: Figure 1 Flow Diagram For Update 2014mentioning
confidence: 99%
“…All but three of these (Lamontagne 1980;Parker 1977b;White 1998) used some form of continuous stimulation, either needle or pressure device. Eight studies combined body and auricular acupuncture (Bier 2002;Han 2006;He 1997;Huang 2012;Labadie 1983;Martin 1981b;Steiner 1982;Vandevenne 1985). Three used continuous stimulation with either indwelling needles (Martin 1981a, Martin 1981b or seeds (He 1997;Huang 2012).…”
Section: Interventionsmentioning
confidence: 99%
“…He et al19 reported that acupuncture treatment showed significant effectiveness in a case-control study, but most other researchers, including Parker et al20 and Steiner et al,21 reported that there was no apparent difference between the control and acupuncture treatment groups. Gillams et al22 also reported no significant difference between the control and acupuncture treatment groups when the acupuncture was applied on remote areas from the lung site of the ear in the control group, that was known as one of the smoking cessation acupuncture points.…”
Section: Discussionmentioning
confidence: 99%
“…The effects did not continue for the one, three and six month followup visits, however, in the Lamontagne et al 44 trial. Steiner et al 45 also noted significant decrease in smoking for acupuncture and sham acupuncture groups, although they didn't find a difference between the groups. Gilliams et al 42 and Parker and Mok 43 reported no difference in smoking behavior between groups.…”
Section: Nicotine Treatmentmentioning
confidence: 95%
“…Eight studies were reviewed. 19,20,[41][42][43][44][45][46] The eight studies are shown in Table 3. Two studies used electroacupuncture 41,43 two used application of a stud needles 42,45 one used a sutured plastic bead on the ear lobe at the acupuncture site, 19 laser acupuncture was used in one study, 20 and two studies used traditional needles 44,46 as the active treatment.…”
Section: Nicotine Treatmentmentioning
confidence: 99%